2011
DOI: 10.1007/s10926-011-9288-2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Remaining at Work with Common Health Problems: What Helps and What Influence Do Organisational Policies Have?

Abstract: The Flags system was useful as a conceptual framework in this context for identifying a number of obstacles to working with health problems, many of which were potentially modifiable on worker, workplace, or wider systems levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…This ties in with the concept of the ''sick role'', which gives an individual who is sick the right to be exempt from social norms and not be blamed for his or her illness, but at the same time obligates him or her to try to get well [36]. This is further exemplified by Holmgren et al [21] who showed that managers were committed to supporting the absent employee during the entire process, but that the managers made demands on the absent employee-asking him/her to take responsibility for rehabilitation and follow regulations.…”
Section: Personal Dilemmas Of the Rtw Policy Enforcermentioning
confidence: 99%
“…This ties in with the concept of the ''sick role'', which gives an individual who is sick the right to be exempt from social norms and not be blamed for his or her illness, but at the same time obligates him or her to try to get well [36]. This is further exemplified by Holmgren et al [21] who showed that managers were committed to supporting the absent employee during the entire process, but that the managers made demands on the absent employee-asking him/her to take responsibility for rehabilitation and follow regulations.…”
Section: Personal Dilemmas Of the Rtw Policy Enforcermentioning
confidence: 99%
“…The role of health professionals in supporting patients on sickness absence to return to work requires further research. [92][93][94][95] There may be a need to examine incentives, and disincentives, to enter return-to-work schemes where there is evidence that interventions are effective in supporting return to work.…”
Section: Research Recommendationsmentioning
confidence: 99%
“…Other prognostic factors, such as the patients' expectation, social background, occupational 'blue flags' and the contextual 'black flags' , might be in place and need further exploration. [16][17][18] The economy might have also contributed to the favourable vocational outcome. However, the annual drop in unemployment (approximately 1%) during the period 19 was much lower than the observed increase in work rate at 1 year (18%), and was probably a minor contribution to the overall improvement.…”
Section: Discussionmentioning
confidence: 99%